Your undergraduate dissertation in health and social care - Walliman, Nicholas; Appleton, Jane V. (Los Angeles ; London : SAGE, 2009)
This title provides a practical, step-by-step guide to both the theoretical and practical aspects of the process of doing an undergraduate dissertation, equipping the reader with all the skills necessary to plan, conduct and write up a research project successfully.
1. What Is a Dissertation? -- 2. What Types of Dissertation Are There? -- 3. What Will it Be About? -- 4. How Do I Get Started? -- 5. What's All This About Philosophy? -- 6. How Do I Write a Proposal? -- 7. What About Working and Planning My Time? -- 8. Where Do I Get Hold of All the Necessary Background Information? -- 9. How Can I Manage All the Notes? -- 10. How Do I Make an Effective Argument? -- 11. What Sorts of Data Will I Find? -- 12. How Do I Critically Appraise Research Evidence? -- 13. What About Research Ethics and Research Governance? -- 14. How Do I Collect Primary Data? -- 15. How Do I Analyse Quantitative Data? -- 16. How Do I Analyse Qualitative Data? -- 17. What About Referencing? -- 18. How Can I Manage a Long Piece of Writing? -- 19. How Can I Make My Work Look Interesting and Easy to Read? -- 20. Who Else Might Be Interested in My Writing?
Keywords: Dissertations, Academic; Medical care; Social service